Introduction to nanofiber materials - Ko, Frank K.; Wan, Yuqin (Cambridge : Cambridge University Press, 2014)
Presenting the latest coverage of the fundamentals and applications of nanofibrous materials and their structures for graduate students and researchers, this book bridges the communication gap between fiber technologists and materials scientists and engineers. Featuring intensive coverage of electroactive, bioactive and structural nanofibers, it provides a comprehensive collection of processing conditions for electrospinning and includes recent advances in nanoparticle-/nanotube-based nanofibers. The book also covers mechanical properties of fibers and fibrous assemblies, as well as characterization methods.
Machine generated contents note: 1. Introduction; 2. Fundamentals of polymers; 3. Nanofiber technology; 4. Modeling and simulation; 5. Mechanical properties of fiber and fiber assemblies; 6. Characterization of nanofibers; 7. Bioactive nanofibers; 8. Electroactive nanofibers; 9. Nanocomposite fibers; 10. Future opportunities and challenges of electrospinning; Index; Appendix I. Terms and unit conversion; Appendix II. Abbreviation of polymers; Appendix III. Classification of fibers; Appendix IV. Polymers and solvents for electrospinning.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Nanofibers -- Industrial applications; Fillers (Materials); Composite materials